2000
DOI: 10.1128/aem.66.12.5348-5352.2000
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Purification, and Characterization of a Killer Protein fromSchwanniomyces occidentalis

Abstract: The yeast Schwanniomyces occidentalis produces a killer toxin lethal to sensitive strains of Saccharomyces cerevisiae. Killer activity is lost after pepsin and papain treatment, suggesting that the toxin is a protein. We purified the killer protein and found that it was composed of two subunits with molecular masses of approximately 7.4 and 4.9 kDa, respectively, but was not detectable with periodic acid-Schiff staining. A BLAST search revealed that residues 3 to 14 of the 4.9-kDa subunit had 75% identity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 46 publications
(45 reference statements)
5
25
0
Order By: Relevance
“…We found that mycocin from the strains Dh-274, Dh-237 andDh-65 exhibited temperature-dependent killer activity against C. albicans up to pH 5.5 and against C. tropicalis up to pH 6.0,with activity decreasing abruptly at nonpermissive temperatures and pH values. Most published studies on mycocin activity report that mycocins are generally stable only over narrow pH ranges and each mycocin has a defined optimal pH for killer activity against the sensitive yeast species (Chen et al, 2000;Soares and Sato, 2000). A previous report by Marquina et al (2001) stated that mycocin from D. hansenii isolated from olive brines had an optimal stability and activity against Candida boidinii (IGC3430) between pH 4.5 and pH 5.1, congruent with our observations.…”
Section: Discussionsupporting
confidence: 81%
“…We found that mycocin from the strains Dh-274, Dh-237 andDh-65 exhibited temperature-dependent killer activity against C. albicans up to pH 5.5 and against C. tropicalis up to pH 6.0,with activity decreasing abruptly at nonpermissive temperatures and pH values. Most published studies on mycocin activity report that mycocins are generally stable only over narrow pH ranges and each mycocin has a defined optimal pH for killer activity against the sensitive yeast species (Chen et al, 2000;Soares and Sato, 2000). A previous report by Marquina et al (2001) stated that mycocin from D. hansenii isolated from olive brines had an optimal stability and activity against Candida boidinii (IGC3430) between pH 4.5 and pH 5.1, congruent with our observations.…”
Section: Discussionsupporting
confidence: 81%
“…These common properties are consistent with the proteinaceous nature of killer toxins, which is also evident from the susceptibility of most toxins to proteolytic enzymes. Most toxins are irreversibly inactivated above pH 5?0 and are stable only in a narrow pH range (Bevan et al, 1973;Chen et al, 2000;Marquina et al, 2001a;Middelbeek et al, 1979;Pfeiffer & Radler, 1984), although the killer toxin from Hansenula saturnus (Ohta et al, 1984) has a broad stability range. Moreover, differences in other properties indicate that the toxins of several yeasts are biochemically distinct (Pfeiffer & Radler, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from protease treatments suggests that Kpkt is a protein with sulfide bonds like several other killer factors (4,35), since papain has been shown to destroy the toxin and its activity. Like most toxins (28), Kpkt is unstable at both high temperatures and high pH values.…”
Section: Discussionmentioning
confidence: 99%